Pengaruh Dana Desa Terhadap Tingkat Kemiskinan di Desa Sidomukti Kecamatan Mootilango Kabupaten Gorontalo - Ainun Atali; Radia Hafid; Sudirman; Meyko Panigoro (Jurnal Pendidikan Ekonomi dan Bisnis, 2025)
This study aimed to determine the Influence of Village Funds on the Poverty Level in Sidomukti Village, Mootilango Sub-discrict, Gorontalo Regency. This study employed a quantitative approach with a survey research method. The primary data were obtained from distributing questionnaires to the recipient of Village Fund Assistance in Sidomukti Village, Mootilango Sub-district, Gorontalo Regency. The samples were 52 respondents, while the data analysis applied simple linear regression.The results show that,Village Funds influence the Poverty Level in Sidomukti Village, Mootilango Sub-district, Gorontalo Regency.The influence of Village funds on the Poverty Level is 24,9%, while the remaining 75,1% is influenced by variables not examined in this current study.